Enhancing the Capacity for Classroom Action Research Utilizing Artificial Intelligence Among Teachers at MAN Bengkayang - Sari, Nopita; Zuraya, Helva (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
Issues Examined in this article: Firstly, the level of comprehension and awareness among teachers at MAN Bengkayang regarding the significance of Classroom Action Research (CAR) in enhancing the quality of education; secondly, the obstacles encountered by teachers at MAN Bengkayang in conducting CAR; thirdly, the identification of effective strategies to improve the capacity of teachers at MAN Bengkayang in implementing AI-based CAR; and fourthly, the extent to which AI-based CAR training programs contribute to the enhancement of teachers' professional competencies at MAN Bengkayang. This article is derived from a community engagement initiative grounded in research utilizing the Participatory Action Research (PAR) methodology. The findings are as follows: first, teachers at MAN Bengkayang exhibit a limited understanding of Classroom Action Research (CAR). Second, teachers at MAN Bengkayang face significant challenges in balancing teaching responsibilities with administrative tasks, which impede the effective implementation of CAR. Third, effective strategies to enhance teachers' competencies in conducting AI-based CAR should encompass technological training, fostering collaboration among teachers, leveraging data for evaluation and feedback, integrating technology into the curriculum, and ensuring the availability of adequate infrastructure. Fourth, AI-based CAR training programs have substantially improved the professional competencies of teachers at MAN Bengkayang. Before participating in the AI-based CAR training, the professional competency of teachers at MAN Bengkayang was assessed at 68.12%, categorized as